Wetting sub-nanochannels via ionic hydration effect for improving charging dynamics - Yayun Shi; Xiaoli Zhao; Qihang Liu; Zhenghui Pan; Congcong Liu; Shanyi Zhu; Zhijun Zuo; Xiaowei Yang (Green Energy & Environment, 2024)
The ionic transport in sub-nanochannels plays a key role in energy storage, yet suffers from a high energy barrier. Wetting sub-nanochannels is crucial to accelerate ionic transport, but the introduction of water is challenging because of the hydrophobic extreme confinement. We propose wetting the channels by the exothermic hydration process of pre-intercalated ions, the effect of which varies distinctly with different ionic hydration structures and energies. Compared to the failed pre-intercalation of SO42−, HSO4− with weak hydration energy results in a marginal effect on the HOMO (Highest Occupied Molecular Orbital) level of water to avoid water splitting during the electrochemical intercalation. Meanwhile, the ability of water introduction is reserved by the initial incomplete dissociation state of HSO4−, so the consequent exothermic reionization and hydration processes of the intercalated HSO4− promote the water introduction into sub-nanochannels, finally forming the stable confined water through hydrogen bonding with functional groups. The wetted channels exhibit a significantly enhanced ionic diffusion coefficient by ∼9.4 times.